The Difference of Anxietys Score and Depressions Score between Mother with Mild Intellectual Disability and Mother with Moderate Intellectual Disability in SLB Negeri Surakarta - Alindina Izzani; Aris Sudiyanto; Dyah Ratna Budiani (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Children with Intellectual Disability (ID) have low Intelligence Quotient (IQ) and low social interaction so that they have difficulty in self-adaptation. Caring for child with disability will increase the risk of psychological morbidity in family such as anxiety and depression especially in mother. This study is aimed to discover the difference of anxietys score and depressions score between mother with mild intellectual disability and mother with moderate intellectual disability. Methods: This study was a cross-sectional observational analytic. 15 mothers of mild intellectual disability (C) and 15 mothers of moderate intellectual disability (C1) were recruited with consecutive sampling from SLB Negeri Surakarta on October 2015. Lie-Minnesota Multyphasic Personality Inventory (L-MMPI), Taylors Manifest Anxiety Scale (TMAS), and Becks Depression Inventory-II (BDI-II) questionnaires were used to assessed anxiety and depression. The test data was broken down and analyzed by independent t-test and the SPSS 20 for Windows software. Results: Mean and deviation TMAS score of mother with mild intellectual disability is 24,937,648 and mother with moderate intellectual disability is 23,009,736. There is no difference of anxietys score between two group of mothers (p = 0,55 ; p > 0,05). Mean and deviation BDI-II score of mother with mild intellectual disability is 11.279.08 and mother with moderate intellectual disability is 10.9310.39. There is no difference of depressions score between two group of mothers (p = 0,92; p > 0,05). Conclusions: There is no difference of anxietys score and depressions score between mother with mild intellectual disability and mother with moderate intellectual disability in SLB Negeri Surakarta. Keywords: Intellectual disability, Anxiety, Depression